2020
DOI: 10.3748/wjg.v26.i26.3834
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced inflammation masks the underlying presence of low-grade dysplasia on gastric lesions

Abstract: BACKGROUND Helicobacter pylori (H. pylori) infection has been associated with a long-term risk of precancerous gastric conditions (PGC) even after H. pylori eradication. AIM To investigate the efficacy of High-Resolution White-Light Endoscopy with Narrow-Band Imaging in detecting PGC, before/after H. pylori eradication. METHODS We studied 85 consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, there is still unresolved debate regarding the best-individualized follow-up strategies, based on malignant risk stratification, due to uncertainty of current evidence and the role of H. pylori inflammatory changes in underestimating IM extension and dysplastic lesions at the index endoscopy (Table 1 )[ 2 - 12 ].…”
Section: To the Editormentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is still unresolved debate regarding the best-individualized follow-up strategies, based on malignant risk stratification, due to uncertainty of current evidence and the role of H. pylori inflammatory changes in underestimating IM extension and dysplastic lesions at the index endoscopy (Table 1 )[ 2 - 12 ].…”
Section: To the Editormentioning
confidence: 99%
“…Notably, a recent prospective cohort study[ 12 ], including 85 Italian patients with H. pylori -related active gastritis, undergoing upper gastrointestinal endoscopy 6 mo following eradication therapy, demonstrated that high-resolution endoscopy with NBI doubled the rate of identifying histological low-grade dysplasia (LGD) missed at pre-treatment endoscopy, in a high-risk subgroup which had extensive atrophy and IM at baseline. In over 40% of patients, visible gastric lesions with LGD were found following H. pylori eradication was not identified at their first pre-treatment endoscopy, thus suggesting that inflammatory changes associated with active H. pylori infection hinder the correct detection of gastric LGD lesions[ 12 ].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations